Bosentan and macitentan prevent the endothelial-to-mesenchymal transition (EndoMT) in systemic sclerosis: in vitro study. Issue 1 (December 2016) - Corallo, Claudio; Cutolo, Maurizio; Kahaleh, Bashar; Pecetti, Gianluca; Montella, Antonio; Chirico, Chiara; Soldano, Stefano; Nuti, Ranuccio; Giordano, Nicola
Abstract Background Systemic sclerosis (SSc) is characterized by early vascular abnormalities and subsequent fibroblast activation to myofibroblasts, leading to fibrosis. Recently, endothelial-to-mesenchymal transition (EndoMT), a complex biological process in which endothelial cells lose their specific markers and acquire a mesenchymal or myofibroblastic phenotype, has been reported in SSc. In the present study, we evaluated the ability of endothelin-1 (ET-1) dual receptor antagonists bosentan (BOS) and macitentan (MAC) to antagonize EndoMT in vitro. Methods Ten women with limited SSc were enrolled. They underwent double skin biopsy (affected and nonaffected skin). Fibroblasts and microvascular endothelial cells (MVECs) were isolated from biopsies. We performed mono- or coculture of MVECs (isolated from nonaffected skin) with fibroblasts (isolated from affected skin and stimulated with ET-1 and transforming growth factor beta [TGF-β]). In cocultures, the MVEC layer was left undisturbed or was preincubated with BOS or MAC. After 48 h of coculture, MVECs were analyzed for their tube formation ability and for messenger RNA and protein expression of different vascular (CD31, vascular endothelial growth factor-A [VEGF-A], VEGF-A165b) and profibrotic (alpha-smooth muscle actin [α-SMA], collagen type I [Col I], TGF-β) molecules. Results After 48 h, MVECs showed a reduced tube formation ability when cocultured with SSc fibroblasts. CD31 and VEGF-A resulted in downregulation, while VEGF-A165b, the antiangiogenic isoform, resulted in upregulation. At the same time, mesenchymal markers α-SMA, Col I, and TGF-β resulted in overexpression in MVECs. Tube formation ability was restored when MVECs were preincubated with BOS or MAC, also reducing the expression of mesenchymal markers and restoring CD31 expression and the imbalance between VEGF-A and VEGF-A165b. Conclusions With this innovative EndoMT in vitro model realized by coculturing nonaffected MVECs with affected SSc fibroblasts, we show that the presence of a myofibroblast phenotype in the fibroblast layer, coupled with an ET-1-TGF-β synergic effect, is responsible for EndoMT. BOS and MAC seem able to antagonize this phenomenon in vitro, confirming previous evidence of endothelium-derived fibrosis in SSc and possible pharmacological interference.